2017
DOI: 10.1007/s00436-017-5582-z
|View full text |Cite
|
Sign up to set email alerts
|

Facultative myiasis of domestic cats by Sarcophaga argyrostoma (Diptera: Sarcophagidae), Calliphora vicina and Lucilia sericata (Diptera: Calliphoridae) in northern Italy

Abstract: We describe five cases of myiasis of domestic cats, Felis silvestris catus L. (Carnivora: Felidae), reported in 2016 in northern Italy and caused by three Diptera species: Sarcophaga argyrostoma (Robineau-Desvoidy) (Sarcophagidae), Calliphora vicina Robineau-Desvoidy and Lucilia sericata (Meigen) (Calliphoridae). Three were cases of traumatic myiasis, one by S. argyrostoma and two by L. sericata, one was a case of auricular myiasis by C. vicina and one was a case of ophthalmomyiasis caused by an association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…of casesSexAgeCountryReference Lucilia sericata and Lucilia ampullacea unk1unkunkAustria[114] L. sericata and Sarcophaga tibialis cut1unkAItaly[116] L. sericata and Calliphora vicina ophth1unkKItaly[117] Abbreviations : ophth, ophthalmic; cut, cutaneous; unk, unknown; A, adult; K, kitten…”
Section: Literature Datamentioning
confidence: 99%
See 2 more Smart Citations
“…of casesSexAgeCountryReference Lucilia sericata and Lucilia ampullacea unk1unkunkAustria[114] L. sericata and Sarcophaga tibialis cut1unkAItaly[116] L. sericata and Calliphora vicina ophth1unkKItaly[117] Abbreviations : ophth, ophthalmic; cut, cutaneous; unk, unknown; A, adult; K, kitten…”
Section: Literature Datamentioning
confidence: 99%
“…The reported cases of myiasis caused by L. sericata in cats occurred in southern and central Europe [108, 111–117], the Middle East [118–123], North America [124] and South America [96, 125]. This species has been found in skin lesions [96, 111, 112, 115–117, 119, 121, 123, 125] caused by traumas such as falls [115], dog bites [116] and car accidents [117], decubitus ulcers and fur soiled by urine and faeces due to neglected conditions [115], old age [117] or postpartum lesions [123]. Lucilia sericata has been reported as agent of urogenital myiasis in three female cats, the first two bearing dead fetuses [118, 122] and the third one with postpartum problems [124].…”
Section: Literature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, myiasis that are well known in medical and veterinary field, are infestations caused by fly larvae that at least for a certain period feed on living or dead tissues, body fluids or ingested food of the host [1]. Many species of Oestridae, Calliphoridae, Sarcophagidae and Muscidae are considered the main agents of myiasis in wild vertebrates, but also farmed and domestic animals and humans [1][2][3][4][5][6][7][8][9]. Myiasis occur in animals when untreated injuries or uro-genital and anal secretions, make the living vertebrate a suitable substrate for fly development.…”
Section: Editorialmentioning
confidence: 99%
“…[8]. Recently, [7] have reported that in cats, decubitus ulceres and exposed wounds are very attractive conditions for facultative-myasis species (e.g. Calliphora vicina, Lucilia sericata (Diptera, Calliphoridae) and Sarcophaga argyrostoma (Diptera, Sarcophagidae).…”
Section: Editorialmentioning
confidence: 99%